Evaluation of the antioxidant and antimicrobial activity of methanolic leaf extracts of Argyreia cuneata (Willd) Ker Gawl - P. Ramesh; S. Veni Madhavi; M. Nagaraju; B. Kiran Kumar (The Bioscan, 2024)
The rising prevalence of antimicrobial-resistant pathogens has underscored the urgent need for new compounds that can effectively combat infectious diseases. A promising source of these compounds lies in the secondary metabolites of species traditionally used for treating such diseases. One such species, Argyreia cuneata, a well- known medicinal plant, has demonstrated significant potential due to its antimicrobial chemical constituents. In this study, we evaluated the antimicrobial activities of methanolic extracts from A. cuneata leaves against various bacterial and fungal strains of therapeutic importance. The analysis revealed that the methanolic leaf extract contained phenolic compounds at a concentration of 2.57%, flavonoids at 1.30%, and exhibited antioxidant activity, as measured by DPPH, at 0.748%. The results indicated that the methanolic leaf extract exhibited robust antimicrobial activity, especially against E. coli. Furthermore, Pseudomonas fluorescens showed high susceptibility to both the methanolic leaf extract and ampicillin. In addition, ketoconazole demonstrated significant inhibitory effects against Fusarium oxysporum and Aspergillus brasiliensis. These findings suggest that the methanolic leaf extract of A. cuneata holds considerable promise as a source of antimicrobial agents. However, to fully harness its potential, further detailed investigation into its chemical composition is essential. This could pave the way for the development of new, effective treatments for combating infectious diseases.